Compound super-oscillation lens for reflective confocal imaging. (July 2023) - Zheng, Pengcheng; Zhu, Zhaoxiang; Pei, Xiangcan; Wu, Qinfei; Liang, Haowen; Chen, Yujie; Li, Juntao; Xie, Xiangsheng
Highlights: We optimize the resolution, signal-to-noise ratio and field of view of the SOL comprehensively by combining with the reflective confocal system for the first time. The imaging performance of the conventional SOL needs to be weighed among the three factors. We realize the reflection confocal microscopy experimentally based on SOL for the first time. The system only needs a single SOL to achieve the functions of excitation and detection so it has significant advantages over transmission CLSM in terms of volume, integration, and flexibility. For the first time, we use a SOL to image a reflective sample rather than a hollow one or fluorescent nanoparticles. Abstract: The super-oscillation lens (SOL) can achieve super-resolution focusing but have to trade-off with weaker hotspots and higher sidebands. We propose a single compound SOL to achieve reflective confocal imaging in principle without additional lenses. The designed SOL consists of an outer lens and an inner lens which play the role of focusing lens and collective lens respectively. As a result, focusing and collecting functions can be simultaneously realized. The improved system can achieve excellent imaging performance with an ultra-high resolution (<0.314λ/NA, NA stands for numerical aperture), and almost negligible side lobe ratio and no side bands, which proved superior to conventional laser scanning confocal microscopy and single SOL. This technology can be attractive for a variety of applications in super-resolution imaging and biomedical sciences.